ACTIVITY MODIFICATION: FROM TRADITIONAL APPROACH TO THE UPDATED METHODS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. This article explores the evolution of teaching practices from traditional methods to computer-assisted (CALL) activities, emphasizing the benefits and challenges of this transformation. It examines activity modification principles, focusing on engagement, accessibility, and personalized learning. The article provides practical examples of how traditional activities like quizzes, group projects, and field trips can be transformed into computer-assisted equivalents. It explores the positive impacts of this shift on student engagement, learning outcomes, and collaboration, while also addressing potential challenges like equity of access and teacher training needs. The conclusion emphasizes balancing traditional and computer-assisted methods to create a holistic and effective learning environment.